2013
DOI: 10.5047/eps.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

First observational study during a solar eclipse event on variations in the horizontal winds simultaneously in the troposphere-stratosphere-mesosphere-lower-thermosphere region over the equatorial station Thumba (8.5°N, 77°E)

Abstract: The longest annular solar eclipse of the millennium occurred on 15 January, 2010, and was visible over the equatorial station Thumba (8.5 • N, 77• E) around noon time. A host of experiments were carried out to study the variations due to the solar eclipse event on various geophysical parameters, from the Earth's surface to ionospheric heights. The present study focuses on the variation in the horizontal winds in the height regions of 0-65 km and 80-100 km, using GPS-sondes, rocket-sondes and meteor wind rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Also, nonstationary oGW can be triggered by wind fluctuations (Chunchuzov, 1994) which are observed in the collected wind data. Nevertheless, other sources of GWs are also plausible, such as triggering of GWs due to the combined effect of wind shears and sudden temperature changes in the lower atmosphere (Ramkumar et al., 2013). This work highlights the necessity of further modeling using 3D simulations including topography to fully understand the generation and propagation of GWs during this and other solar eclipses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, nonstationary oGW can be triggered by wind fluctuations (Chunchuzov, 1994) which are observed in the collected wind data. Nevertheless, other sources of GWs are also plausible, such as triggering of GWs due to the combined effect of wind shears and sudden temperature changes in the lower atmosphere (Ramkumar et al., 2013). This work highlights the necessity of further modeling using 3D simulations including topography to fully understand the generation and propagation of GWs during this and other solar eclipses.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature perturbation was set to −4% which is equivalent to a maximum perturbation of −11°C at ∼50 km but only of −7°C at ∼90 km (Figure 7a, shaded region). Lower atmospheric adiabatic heating effects were disregarded (Ramkumar et al., 2013) because we found that temperature perturbations in the troposphere did not produce large changes in TC. Previous studies show that eclipse‐induced wind perturbations can vary significantly.…”
Section: The Effect Of the Tse On The Vertical Energy Fluxmentioning
confidence: 99%
“…We suggest that this TEC enhancement over the Rocky Mountains is caused by processes triggered by the eclipse, perhaps due to large temperature changes on the ground that induced or enhanced locally produced atmospheric waves in the mountain region. Large changes in mesosphere-lower thermosphere (MLT) zonal winds during eclipses have been observed by Ramkumar et al (2013). They observed a reversal of zonal winds at 98 km during the maximum phase of the January 2010 eclipse at local noon.…”
Section: Eclipse-induced Ionospheric Disturbancesmentioning
confidence: 97%
“…Ramkumar et al . [], studying the same event over Trivandrum, reported enhanced gravity wave amplitudes with short vertical wavelengths of 2–8 km throughout the troposphere and stratosphere. They have also reported enhancement in amplitudes of periods in the range of 80–100 min using meteor radar data in the mesosphere/lower thermosphere (MLT) region.…”
Section: Discussionmentioning
confidence: 96%
“…Further, Ramkumar et al . [] have also reported that the wave propagates upward from the region below 80 km and downward from the region above 98 km indicative of the fact that there are two source regions one above 100 km and one below 80 km height region. The present study is in agreement with the above observations.…”
Section: Discussionmentioning
confidence: 96%